Inclusão de crianças com Transtorno do Espectro Autista na Educação Infantil: o desafio da formação de professoras - Roberta Flavia Alves Ferreira (2017)
This study aims at analyzing the type of training that teachers who work in a Municipal Infant Education Unit (UMEI), in the city of Belo Horizonte, received during their initial training and throughout their professional career and how they evaluate this training before of the challenge of ensuring the inclusion of children with Autism Spectrum Disorder. The UMEI surveyed is located in a suburb of Belo Horizonte, in the North Region of the city. As a research methodology, a qualitative approach was chosen, using a case study. A bibliographical and documentary survey was carried out in the search for legal and normative concepts and documents at the international, national and local levels essential for theoretical construction. As a research technique, the interview and the focus group were used. Among the analyzes carried out, it was highlighted the recognition that it is incumbent upon the Infant Education teacher to promote and / or facilitate the interaction of children with autism with their peers. It was identified the need for teachers to deepen their understanding of educational and learning needs by accessing refresher courses and appropriate materials for specific activities directed at autistic children. It was found that teachers do not feel prepared to work with children with Autism Spectrum Disorder (ASD) because of lack of knowledge about the particularities of the disability and of not receiving specific training on the inclusion of children with ASD. In view of the unpreparedness and insecurity reported by the teachers to work with children with autism and due to the absence of continuing education courses that overcome these shortcomings, a primer was developed to assist the teachers who have students with autism in their classes to understand More about the deficiency and ways of intervening pedagogically with these children. At the end of the study it was concluded that for enrollment to actually take place, it is not enough merely to ensure the enrollment of students with disabilities in regular education. Without the curricular adequacy, individualized educational planning, specific pedagogical resources and, mainly, continuous formation of the teachers, the inclusion is not effective.